A bibliometric analysis of blockchain's potential to transform accounting and auditing: Patterns and perspectives - Siregar, Muhammad Ichsan; Hamidah, Hamidah (International Journal of Innovative Research and Scientific Studies, 2025)
This study uses a literature review methodology to examine how blockchain technology is transforming accounting and auditing. The R Studio tool is utilized to support the bibliometric approach, which is based on information taken from the Scopus database. 351 documents were selected based on the business, management, and accounting domains from the original 994 documents that were discovered using specific keywords. Following additional screening, bibliometric analysis was performed on 348 documents. The findings demonstrated that blockchain plays a significant role in enhancing the security and quality of accounting data as well as propelling the field's evolution towards the incorporation of new technologies, sustainability concerns, and research avenues focused on investment, economic analysis, and sustainable development. Furthermore, this technology offers substantial advantages in commerce and supply chain management. This study's distinctive contribution is its mapping of current research patterns that demonstrate how blockchain is starting to influence the field of modern accounting and auditing. To sum up, the implementation of blockchain technology has the potential to improve accounting and auditing processes overall. It is advised that future studies examine how blockchain is used in data management across businesses and how it affects the accounting and auditing industry economically on a large scale.